0

# what is the answer to -6(x+9)

i need to simplify this.

thank ya'll so much

### 3 Answers by Expert Tutors

BRUCE S. | Learn & Master Physics & Math with Bruce SLearn & Master Physics & Math with Bruce...
4.9 4.9 (36 lesson ratings) (36)
0

If expression was actually worded equal to zero the solution is as follows

-6(x+9)= 0

-6x + -6*9= 0    expand the left side

-6x + -54 = 0   calculate expressions inside left side

x + 9 =0          divide both sides by -6

x = -9              solution

CHECK:   -6(x+9)= 0 @ x= -9 =>  -6(-9 + 9) = 0   correct because -9 +9  = 0  &  -6*0=0

Nikoli W. | The Best, Young Tutor AroundThe Best, Young Tutor Around
0

To simplify, you need to distribute the -6 through to the expression within the parentheses.

-6(x+9)=
-6(x) + -6(9)= -6x-54

This is the only way to really simplify the expression you gave.

Kevin S. |
5.0 5.0 (4 lesson ratings) (4)
0
Using the distributive property, the -6 is multiplied by x and also multiplied by 9: (-6)(x) + (-6)(9) = -6x -54